The computational power of Watson-Crick grammars: Revisited - Mohamad Zulkufli, Nurul Liyana; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Messikh Azeddine, Azeddine (2016)
A Watson-Crick finite automaton is one of DNA computational models using the Watson-Crick complementarity feature of deoxyribonucleic acid (DNA). We are interested in investigating a grammar counterpart of Watson-Crick automata. In this paper, we present results concerning the generative power of Watson-Crick (regular, linear, context-free) grammars. We show that the family of Watson-Crick context-free languages is included in the family of matrix languages.